2009
DOI: 10.1007/s10236-009-0194-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impact of wind and waves on suspended particulate matter fluxes in the East Frisian Wadden Sea (southern North Sea)

Abstract: Suspended particulate matter (SPM) fluxes and dynamics are investigated in the East Frisian Wadden Sea using a coupled modeling system based on a hydrodynamical model [the General Estuarine Transport Model (GETM)], a third-generation wave model [Simulating Waves Nearshore (SWAN)], and a SPM module attached to GETM. Sedimentological observations document that, over longer time periods, finer sediment fractions disappear from the Wadden Sea Region. In order to understand this phenomenon, a series of numerical sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…The positive relation between SPM concentrations and higher wind speeds was found by several researchers (e.g. Badewien et al 2009;Stanev et al 2009;Bartholomä et al 2009;Lettmann et al 2009). However, even when weather conditions were similar, winter SPM concentrations were higher (Grossart et al 2004).…”
Section: Seasonal Variationsupporting
confidence: 58%
See 2 more Smart Citations
“…The positive relation between SPM concentrations and higher wind speeds was found by several researchers (e.g. Badewien et al 2009;Stanev et al 2009;Bartholomä et al 2009;Lettmann et al 2009). However, even when weather conditions were similar, winter SPM concentrations were higher (Grossart et al 2004).…”
Section: Seasonal Variationsupporting
confidence: 58%
“…The variation in tidal level depends on the location: the highest tidal ranges in the Wadden Sea are found in the corner of the German Bight (>3 m) and the least diVerences are found near the islands Texel and Fanø (»1.5 m) (Postma 1982;Dijkema et al 1980). Storm events alter the water level and thus also the water depth in the tidal area (Stanev et al 2009;Lettmann et al 2009). While most South-westerly storms will elevate the water level, strong easterly wind will lower the water level signiWcantly.…”
Section: Tidal Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the storm surge, unusually high waves have been measured in the southern North Sea developing on northern North Sea and propagated southward under the influence of strong north winds with a long fetch. The storm Britta has been given particular attention in our analyses for the types of changes that may occur during single event (Bartholomä et al, 2009;Lettmann et al, 2009;Stanev et al, 2011;Grashorn et al, 2015).…”
Section: Coupled Model Implementation and Periods Of Analysesmentioning
confidence: 99%
“…The ocean waves affect not only the sea level but also the currents and mixing, the latter being of utmost importance for the sediment dynamics (Lettmann et al, 2009). Prandle et al (2000) demonstrated the need of accounting for surface waves with a significant wave height larger than one metre in the sediment modelling.…”
Section: Introductionmentioning
confidence: 99%